2015
DOI: 10.1016/j.ijpddr.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of the antiplasmodial activity of tryptanthrin derivatives

Abstract: HighlightsWe report the synthesis of tryptanthrin derivatives.We report the activity of tryptanthrin derivatives against Plasmodium falciparum.We discuss the potential of tryptanthrin derivatives as multi-stage drugs.We recommend the formulation and testing of tryptanthrins in in vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…We transferred 100 μl of the supernatant to another new microtiter plate. The absorbance of free hemoglobin was measured at 550 nm (Onambele et al, ). The hemolytic rate was calculated using the 0.1% Triton X‐100 positive control for hemolysis of human RBCs, which was considered 100%.…”
Section: Methodsmentioning
confidence: 99%
“…We transferred 100 μl of the supernatant to another new microtiter plate. The absorbance of free hemoglobin was measured at 550 nm (Onambele et al, ). The hemolytic rate was calculated using the 0.1% Triton X‐100 positive control for hemolysis of human RBCs, which was considered 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Structural modification of natural compounds can increase compound potency and selectivity, enhance their pharmacological properties, and significantly diminish their detrimental effects ( Guo, 2017 ). Several TRYP derivatives with various tetracyclic scaffold modifications have been developed, including compounds with anti-plasmodium and anti-toxoplasma properties ( Krivogorsky et al., 2008 ; Onambele et al., 2015 ), indoleamine 2,3-dioxygenase inhibitors ( Yang et al., 2013 ), and DNA triplex stabilizing agents ( Chen et al., 2007 ). Recently, we found that tryptanthrin-6-oxime (TRYP-Ox) had high affinity for JNK1-3 and also blocked activation of NF-κB/AP-1 and the production of IL-6 by lipopolysaccharide-treated monocytic cells ( Schepetkin et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quinazoline alkaloid, tryptanthrin and its synthetic derivatives designated NT1 and T8, have significant gametocytocidal activity in vitro (Figure 3, Table 2, Table S1) [95]. However, of the three agents only NT1 strongly inhibited exflagellation of micro-gametes (Table S1) [95]. Cryptolepine and a root extract of its parent plant, Cryptolepis sanguinolenta (Lindl.)…”
Section: Alkaloids Steroids and Miscellaneousmentioning
confidence: 99%
“…Other alkaloids including dihydronitidine and heitziquinone, isolated from the plant species Zanthoxylum heitzii (Rutaceae), also showed activity against ookinete development in vitro [ 94 ]. The quinazoline alkaloid, tryptanthrin and its synthetic derivatives designated NT1 and T8, have significant gametocytocidal activity in vitro ( Figure 3 , Table 2 , Table S1 ) [ 95 ]. However, of the three agents only NT1 strongly inhibited exflagellation of micro-gametes ( Table S1 ) [ 95 ].…”
Section: Effectiveness Of Natural Products Against Transmission-blmentioning
confidence: 99%